2021
DOI: 10.4236/ojoph.2021.113017
|View full text |Cite
|
Sign up to set email alerts
|

Visual Performance of a Polynomial Extended Depth of Focus Intraocular Lens

Abstract: Purpose: To clinically evaluate a new extended depth of focus intraocular lens (ISOPURE, PhysIOL) with optic design modification based on a unique polynomial concept to improve intermediate vision while keeping the quality of distance vision equal to a monofocal lens. Methods: 18 patients (11 female, 7 male, mean age of 69.4 years) with bilateral cataract and regular corneal astigmatism ≤ 1.0 D underwent bilateral cataract surgery with ISOPURE implantation. Patients were followed for up to 6 months. Measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…Stodulka and Slovak [ 20 ] recently published the clinical outcomes of patients implanted with the IsoPure IOL. Their clinical study confirmed the predicted gain at intermediate and comparable visual acuity at distance and normal contrast sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stodulka and Slovak [ 20 ] recently published the clinical outcomes of patients implanted with the IsoPure IOL. Their clinical study confirmed the predicted gain at intermediate and comparable visual acuity at distance and normal contrast sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Son et al showed that the EDOF IOL group had better-uncorrected distance visual acuity than the monofocal lens group for the unexpected postoperative residual refractive errors like spherical equivalent values of +0.50 D or −0.50 D [ 22 ]. Stodulka and Slovak [ 20 ] published the visual acuity obtained with the IsoPure IOL after the induction of different values of the positive and negative cylinder and showed that it dependent on the axis, with superior vision at an axis 180° and similar results at axis of 90° in comparison to the multifocal IOLs. Residual cylinders from +1.0 D to −1.25 D should therefore have no significant impact on visual acuity (better than 0.2 logMAR), and patient satisfaction and the lens may present an advantage.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is one in-vitro study 20 and two clinical studies with small samples. 17 , 18 Łabuz et al 20 performed an in-vitro comparison of four EDOF IOLs [Tecnis Eyhance ICB00 (Johnson and Johnson), AE2UV/ZOE (Eyebright Medical Technology), RayOne EMV (Rayner) and the isofocal EDOF lens (BVI)] and a standard monofocal lens [Tecnis ZCB00 (Johnson and Johnson)]. They found that the performance of the isofocal EDOF lens at −1.0 D was superior to that of the monofocal IOL.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are clinically confirmed by the defocus curve in our study (see Figure 4 ). Stodulka et Slovak 17 studied 18 patients implanted with the isofocal EDOF lens 4–6 months after surgery. In another small clinical study (n=21), Bova and Vita 18 compared the isofocal EDOF lens with a monofocal IOL (Tecnis PCB00).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation